Enriching knowledge management in research & development organization: A Malaysian perspective - Ibrahim, Amlus; Faisal Mohamed, Nur Fadziana; Ramayah, T.; Saad, Abd. Rahim (2006)
The paper study on the knowledge management in utilization of information communication and technology, hereinafter called ICT, in research and development organization In a turbulent and rapidly changing environment, every organization faces the challenge of how to best manage its knowledge assets to generate value for the marketplace and obtain competitive advantage Such advantage derives from special capabilities that are rare, valuable, non-substitutable, and costly to imitate Historically, the focus was on capabilities involving tangible assets; now, knowledge is widely recognized as the source for competitive advantage, with the tangible assets representing the physical manifestation of but a fraction of this knowledge As companies scramble to develop strategies for more proactive& and strategically managing their knowledge, the field of knowledge management (KM) receives increasing attention from trade organizations and academic journals.From this study it was found that to improve the chances of conclusively demonstrating value to the overall business enterprise, a new KM implementation in an innovation organization should address six imperatives: instill the organization's goals and strategies, access tacit knowledge, provide search tools, promote creativity, capture new learning and build a supportive culture.